Genomic and functional evaluation of TNFSF14 in multiple sclerosis susceptibility. (20th June 2021) - Zuccalà, Miriam; Barizzone, Nadia; Boggio, Elena; Gigliotti, Luca; Sorosina, Melissa; Basagni, Chiara; Bordoni, Roberta; Clarelli, Ferdinando; Anand, Santosh; Mangano, Eleonora; Vecchio, Domizia; Corsetti, Elena; et al.
Abstract: Among multiple sclerosis (MS) susceptibility genes, the strongest non-human leukocyte antigen (HLA) signal in the Italian population maps to the TNFSF14 gene encoding LIGHT, a glycoprotein involved in dendritic cell (DC) maturation. Through fine-mapping in a large Italian dataset (4, 198 patients with MS and 3, 903 controls), we show that the TNFSF14 intronic SNP rs1077667 is the primarily MS-associated variant in the region. Expression quantitative trait locus (eQTL) analysis indicates that the MS risk allele is significantly associated with reduced TNFSF1 4 messenger RNA levels in blood cells, which is consistent with the allelic imbalance in RNA-Seq reads ( P  < 0.0001). The MS risk allele is associated with reduced levels of TNFSF14 gene expression ( P  < 0.01) in blood cells from 84 Italian patients with MS and 80 healthy controls (HCs). Interestingly, patients with MS are lower expressors of TNFSF14 compared to HC ( P  < 0.007). Individuals homozygous for the MS risk allele display an increased percentage of LIGHT-positive peripheral blood myeloid DCs (CD11c +, P  = 0.035) in 37 HCs, as well as in in vitro monocyte-derived DCs from 22 HCs ( P  = 0.04). Our findings suggest that the intronic variant rs1077667 alters the expression of TNFSF14 in immune cells, which may play a role in MS pathogenesis.